The brain digitalization: it's all happening so fast! - Boulos, Laura-Joy (Frontiers in Human Dynamics, 2024)
The use of tech in mental health has drastically increased in the recent years. Indeed advances in technology have made it possible to better characterize, predict, prevent, and treat a range of psychiatric illnesses. What is less paid attention to however is the impact of tech on our mental health and brain functioning, or what we have called, the digitalization of our brains. The acceleration of tech is correlated with an increased prevalence of reported mental health disorders. The overuse of technology and social media is also correlated to cognitive and affective alterations in apparently healthy individuals, including increased feelings of isolation, stress, memory and attention deficits, as well as modifications in information and reward processing. In this review we discuss the impact of technology on our mental health and brains, emphasizing on the need to take into account our brain capacities in order to optimize the integration of tech in our daily lives all while preserving our core cognitive functions.